2021
DOI: 10.1186/s13073-021-00946-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing DNA methylation signatures and their potential functional roles in Merkel cell carcinoma

Abstract: Background Merkel cell carcinoma (MCC) is a rare but aggressive skin cancer with limited treatment possibilities. Merkel cell tumors display with neuroendocrine features and Merkel cell polyomavirus (MCPyV) infection in the majority (80%) of patients. Although loss of histone H3 lysine 27 trimethylation (H3K27me3) has been shown during MCC tumorigenesis, epigenetic dysregulation has largely been overlooked. Methods We conducted global DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…One study found an association between hypomethylation at PD-1 gene in relation to patient outcome, when used as prognostic marker [ 119 ], while a lack of diagnostic significance has been reported for several candidate genes, such as p14 ARF /CDKN2A , MGMT , PTCH1, and members of the RASSF family [ 113 , 115 , 116 , 117 , 118 ]. The potential diagnostic and prognostic utility of KDM6B gene hypomethylation in MCPyV-driven MCC management has also been pointed out [ 121 ]. No data have been reported on DNA methylation as a therapy target for MCPyV-driven MCC.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found an association between hypomethylation at PD-1 gene in relation to patient outcome, when used as prognostic marker [ 119 ], while a lack of diagnostic significance has been reported for several candidate genes, such as p14 ARF /CDKN2A , MGMT , PTCH1, and members of the RASSF family [ 113 , 115 , 116 , 117 , 118 ]. The potential diagnostic and prognostic utility of KDM6B gene hypomethylation in MCPyV-driven MCC management has also been pointed out [ 121 ]. No data have been reported on DNA methylation as a therapy target for MCPyV-driven MCC.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…A recent analysis reported hypermethylation of RASSF2/-5C/-10 genes ranging from 7-23% in MCCs and absent in normal tissues, while no correlation between RASSFs methylation status and MCC characteristics (primary vs. metastatic), or MCPyV-positivity, was found [ 116 ]. The DNA methylation profile has been recently investigated in MCPyV-positive and -negative primary and metastatic MCC tumors and cell lines compared with paired normal tissues [ 121 ]. Specific DNA methylation patterns exhibiting potential clinical relevance for MCC management and correlating with MCC onset, MCPyV gene expression, neuroendocrine features, and H3K27me3 status have been described [ 121 ].…”
Section: Epigenetic Dysregulations In Merkel-cell-polyomavirus-driven Merkel Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the direct use of tumor samples would certainly have advantages; however, cell lines are extremely useful for determining cell origin patterns as they do not suffer from sample impurity. Two recent studies addressed differences in DNA-methylation between VP- and UV-MCCs using either MCC tissue or cell lines [ 56 , 57 ]. Consistent with the here reported results, both studies found a relatively low number of DMPs (470 and 2260) with the majority of DMPs being hypomethylated in VP-MCC samples in these reports as well.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the here reported results, both studies found a relatively low number of DMPs (470 and 2260) with the majority of DMPs being hypomethylated in VP-MCC samples in these reports as well. However, neither group inferred tissue of origin signatures since clustering of MCC with samples from dermis, epidermis, and nerve tissues resulted in a clear separation of MCC tissues or because MCC cell lines clustered together with other neuroendocrine entities [ 56 , 57 ]. The PCA derived scoring of the present study allowed conclusion on the tissue of origin by deconvolution of the data into its underlying components, exploiting the purity of cell lines.…”
Section: Discussionmentioning
confidence: 99%